2019
DOI: 10.1002/14651858.cd005619.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Subacromial decompression surgery for rotator cuff disease

Abstract: Background Surgery for rotator cuff disease is usually used after non-operative interventions have failed, although our Cochrane Review, first published in 2007, found that there was uncertain clinical benefit following subacromial decompression surgery. Objectives To synthesise the available evidence of the benefits and harms of subacromial decompression surgery compared with placebo, no intervention or non-surgical interventions in people with rotator cuff disease (excluding full thickness rotator cuff tears… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
95
1
6

Year Published

2019
2019
2021
2021

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 85 publications
(105 citation statements)
references
References 91 publications
3
95
1
6
Order By: Relevance
“…Parallel teams conducted these systematic reviews 1415. Another team updated a Cochrane systematic review synchronised with this BMJ Rapid Recommendation 16. The panel asked the review team to explore potential subgroup effects for risk of bias in trials and different types of comparisons to surgery, such as exercise therapy.…”
Section: Current Practicementioning
confidence: 99%
“…Parallel teams conducted these systematic reviews 1415. Another team updated a Cochrane systematic review synchronised with this BMJ Rapid Recommendation 16. The panel asked the review team to explore potential subgroup effects for risk of bias in trials and different types of comparisons to surgery, such as exercise therapy.…”
Section: Current Practicementioning
confidence: 99%
“…10 Nevertheless, a recent Cochrane review concluded that "some people will derive substantial benefit with pregabalin; more will have moderate benefit, but many will have no benefit or will discontinue treatment". 11 In approximately 60% of cases, PNP is localized, affecting a specific and limited area of the body. 3 In the case of localized PNP, it is prudent to consider a local treatment such as a lidocaine 5% patch or capsaicin.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, RCTs focused on shoulder pain with intact rotator cuff tendons were excluded [188]. High-certainty evidence shows that subacromial decompression does not provide clinically important benefits over placebo in pain, function, or health-related quality of life [189].…”
Section: Discussionmentioning
confidence: 99%